Re-evaluation of deep-sea dogfishes (genus Squalus) in Japan using phylogenetic inference. (June 2020) - Ziadi-Künzli, F.; Soliman, T.; Imai, H.; Sakurai, M.; Maeda, K.; Tachihara, K.
Abstract: Japan is known for its marine biodiversity and diverse ecosystem due to its unique geological composition and water currents creating suitable habitats for a wider range of marine species. A rich deep-sea shark community with high endemism occurs on the continental shelf. Yet, the deep-sea shark taxonomy is still under development and poorly documented. Here, a DNA barcoding technique was adopted using the mitochondrial cytochrome oxidase I (COI) and NADH2 genes of samples collected from Japan with additional samples from genetic databases to draft out a phylogenetic tree of the deep-sea shark genus Squalus (dogfishes). The morphological divergence of congeners was further examined. Bayesian and maximum-likelihood-based species-level phylogenetic analyses of mitochondrial COI, ND2 and combined sequences provided strong support for distinct clades corresponding to the parental species with substantial sequence divergence between parental species. The combined dataset of the COI and ND2 gene was most suitable for barcoding of Squalus dogfishes. A multivariate analysis of morphological traits was largely consistent with the genetic data showing small but discrete differences in phenotypic characteristics allowing to separate Squalus species. Genetic samples of the taxonomically problematic Shortspine spurdog ' Squalus mitsukurii ' from the Atlantic Ocean and Taiwan did not match with the type material of S. mitsukurii Jordan & Snyder, 1903 from mainland Japan. Squalus mitsukurii once considered a globally distributed species is a single, unique spurdog restricted to temperate Japan and Korea and may present an endemic in the Northwestern Pacific. This study further resolved two genetically and phenotypically distinct species of Squalus dogfishes in Japan, one in sympatry with S. mitsukurii in mainland Japan and one in sympatry with subtropical waters associated congeners in the Ryukyu Archipelago. The occurrence of populations of the 'high-fin' Taiwan spurdog, Squalus formosus, in subtropical Japan is herein confirmed. Graphical abstract: Image 1 Highlights: Reconstructed phylogeny of the deep-sea shark genus Squalus using mitochondrial genes. Support for taxonomic separation of Shortspine spurdog S. mitsukurii as an endemic to the Western North Pacific. Morphological assessment supports molecular separation. Revelation of hidden diversity with high local endemism and occurrence of disjunct distribution pattern within the genus. Underestimated diversity and limited distribution ranges presents a challenge in terms of resilience and shark conservation.